Gender, ethnic and age diversity and performance of large Malaysian firms (Kepelbagaian jantina, kumpulan etnik, dan umur dalam lembaga pengarah firma besar di Malaysia dan prestasi) - Abdullah , Shamsul Nahar (Institut Aminuddin Baki MOEM, 2013)
Board diversity is important especially in countries which practice a one-tier board system, such as Malaysia. Under the system, board appointments are usually controlled by the firm’s substantial shareholders, and as a result, directors are chosen based on “the old-boy” network or “people like us”, who are typically middle-aged males and from similar ethnicity which could lead to “group think”. Board diversity ensures breadth and depth of the board’s judgments. To this end, this study examines board diversity of the top 100 non-financial Malaysian firms, specifically directors’ gender, ethnicity and age and their effects on firm performance. Data are collected from the 2007 annual reports of the sample firms. The evidence indicates the lack of diversity of the Malaysian boards of directors. Results from the multivariate analyses reveal that gender diversity is negatively associated with Tobin’s q and ROA. Age diversity is found to be negatively related to ROA. Ethnic diversity, on the other hand, is found to be positively associated with ROA. Hence, findings on the effect of board diversity and firm performance are mixed. Nevertheless, this study offers insights to policy makers in enhancing corporate governance in Malaysia where diversity is one of the areas that could strengthen the effectiveness of the board.